Associations of drinking water and urinary uranium with incident diabetes among U.S. adults: The Multi-Ethnic Study of Atherosclerosis and the Strong Heart Family Study - Maya Spaur; Kathrin Schilling; Ronald A. Glabonjat; Anirban Basu; Kevin P. Patterson; Wil Lieberman-Cribbin; Qixuan Chen; Filippo Ravalli; Marta Galvez-Fernandez; Pam Factor-Litvak; Steven Chillrud; Benjamin C. Bostick; et al. (Environmental Research, 2026)

An Extended-Release Injectable Suspension of Meloxicam for Pain Management in Veterinary Applications - Sruthi Turaga; Daniel Yong; Guru Raghavendra Valicherla; Steven Leary; Susan Witham; Barry Levinson; Lisa Rohan; Sravan Kumar Patel (Journal of Pharmaceutical Innovation, 2026)

Stone artefacts on the seabed at a submerged freshwater spring confirm a drowned cultural landscape in Murujuga, Western Australia - Jonathan Benjamin; Michael O'Leary; John McCarthy; Wendy Reynen; Chelsea Wiseman; Jerem Leach; Simon Bobeldyk; Justine Buchler; Philippe Kermeen; Michelle Langley; Adam Black; Hiro Yoshida; et al. (Quaternary Science Reviews, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Assessing vertebrate biodiversity in a kelp forest ecosystem using environmental DNA - Jesse A. Port; James L. O'Donnell; Ofelia C. Romero‐Maraccini; Paul R. Leary; Steven Y. Litvin; Kerry J. Nickols; Kevan M. Yamahara; Ryan P. Kelly (Molecular Ecology, 2016)
Preserving biodiversity is a global challenge requiring data on species’ distribution and abundance over large geographic and temporal scales. However, traditional methods to survey mobile species’ distribution and abundance in marine environments are often inefficient, environmentally destructive, or resource‐intensive. Metabarcoding of environmental DNA ( eDNA ) offers a new means to assess biodiversity and on much larger scales, but adoption of this approach for surveying whole animal communities in large, dynamic aquatic systems has been slowed by significant unknowns surrounding error rates of detection and relevant spatial resolution of eDNA surveys. Here, we report the results of a 2.5 km eDNA transect surveying the vertebrate fauna present along a gradation of diverse marine habitats associated with a kelp forest ecosystem. Using PCR primers that target the mitochondrial 12S rRNA gene of marine fishes and mammals, we generated eDNA sequence data and compared it to simultaneous visual dive surveys. We find spatial concordance between individual species’ eDNA and visual survey trends, and that eDNA is able to distinguish vertebrate community assemblages from habitats separated by as little as ~60 m. eDNA reliably detected vertebrates with low false‐negative error rates (1/12 taxa) when compared to the surveys, and revealed cryptic species known to occupy the habitats but overlooked by visual methods. This study also presents an explicit accounting of false negatives and positives in metabarcoding data, which illustrate the influence of gene marker selection, replication, contamination, biases impacting eDNA count data and ecology of target species on eDNA detection rates in an open ecosystem.

Phylogenetic Distribution and Identification of Fin-winged Fruits - Steven R. Manchester; Elizabeth L. O’Leary (The Botanical Review, 2010)